A CO emission-based adaptive signal control for isolated intersections. (4th May 2021) - Lertworawanich, Ponlathep; Unhasut, Panumas
ABSTRACT: Rapid economic growth in recent decades has led to a rising motorization and congestion in urban areas. Congestion at intersections is considered as the prime source of emissions. This study presents a CO emission-based adaptive signal control for isolated intersections. Traffic dynamics at signalized intersections are modeled on the time–space diagrams using the shockwave theory and information from loop detectors installed upstream of intersections. Emissions are estimated from the sum of the product of emission rates and times spent by vehicles in each operating mode. With the assumption that traffic demand remains the same in the next cycle, a split adjustment policy is established by incrementally adjusting splits so that the total intersection emissions gradually reduce. Cycle length is adjusted in the next cycle by evaluating the residual queues. Efficiency of the proposed control algorithm is investigated via simulation. It is found that when the sum of flow ratios of the critical movements is between 0.6 and 1.0, the proposed adaptive control produces smaller CO emissions, delay, and stop than the Webster fixed-time control does with the 0.025 level of significance. On average, the proposed control algorithm can reduce CO emissions by 7.67% when compared to the Webster fixed-time signal settings. However, the reduction depends on the sum of flow ratios. Implications : Congestion at intersections is considered as the prime source of emissions. This study presents an emission-based adaptive signal control for isolated intersections with an aim at reducing CO emissions in urban areas. The proposed control method uses occupancy information obtained from loop detectors to construct the time-space diagrams using the shockwave theory while most existing signal control algorithms rely on flow information to calculate signal timing. A simple feedback control policy for signal timing adjustment is presented. It is found that the proposed algorithm can help reducing emissions at signalized intersections in urban areas.